2011
DOI: 10.3390/molecules16097357
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Aristolochia brevipes against Multidrug-Resistant Mycobacterium tuberculosis

Abstract: The increased incidence of Multidrug-Resistant Mycobacterium tuberculosis (MDR-MT) requires the search for alternative antimycobacterial drugs. The main aim of this study was to evaluate the dichloromethane extract from Aristolochia brevipes (Rhizoma) and the compounds isolated from this extract against several mycobacterial strains, sensitive, resistant (monoresistant), and clinical isolates (multidrug-resistant), using the alamarBlue™ microassay. The extract was fractionated by column chromatography, yieldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Aristolochic acids, isolated from this plant inhibited Escherichia coli , Pseudomonas aeruginosa , Streptococcus faecalis , Staphylococcus aureus and Staphylococcus epidermidis [ 22 ]. Several plant extracts from the genus Aristolochia have been shown to possess strong in vitro antimicrobial activity [ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aristolochic acids, isolated from this plant inhibited Escherichia coli , Pseudomonas aeruginosa , Streptococcus faecalis , Staphylococcus aureus and Staphylococcus epidermidis [ 22 ]. Several plant extracts from the genus Aristolochia have been shown to possess strong in vitro antimicrobial activity [ 23 - 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…36 Stigmasterol has an MIC of 100 µg/mL 37 and 1:1 mixture of stigmasterol and sitosterol has an MIC of 12.5 µg/mL against M. tuberculosis. 38 To our knowledge, this is the first study reporting the antitubercular activity of the hexane extract of the fruit of A. marmelos and we have identified six active principles in it which inhibited the growth of the virulent strain of M. tuberculosis. A recent study which analyzed the anti-TB activity of the n-butanol extract of A. marmelos fruit pulp has also discovered marmin as one of the active compounds against avirulent M. tuberculosis H37Ra and M. bovis.…”
Section: Discussionmentioning
confidence: 82%
“…Compound 2 was finally evaluated with the Microplate Alamar Blue Assay (MABA) method to determine its antituberculous activity, and the result showed that this metabolite (MIC, 3.125 µg/mL) was more active than its parent compound 1 (MIC, 25 µg/mL, [ 13 ]) against Mycobacterium tuberculosis H37Rv.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies conducted on this plant species report the presence of 9-methoxytariacuripyrone ( 1 ) and 7,9-dimethoxy-tariacuripyrone [ 10 ], as well as aporfinic alkaloids such as 6a,7-dehydro- N -formylnornantenine, N -formylnornantenine, and aristololactame I [ 12 ]. Additionally, the anti-tuberculous activity of these compounds has been reported [ 13 ].…”
Section: Introductionmentioning
confidence: 99%